Concordant patterns of genetic, acoustic, and morphological divergence in the West African Old World leaf‐nosed bats of the Hipposideros caffer complex. (29th July 2021) - Baldwin, Heather J.; Vallo, Peter; Ruiz, A. Tonatiuh; Anti, Priscilla; Nkrumah, Evans E.; Badu, Ebenezer K.; Oppong, Samuel K.; Kalko, Elisabeth K. V.; Tschapka, Marco; Stow, Adam J.
Abstract: Levels of biodiversity are globally underestimated, especially in tropical ecosystems. This is particularly so for bats compared to other mammalian taxa, due to morphological conservatism. Here, we investigate West African bats of the Hipposideros caffer complex, an insectivorous bat group occurring throughout the Afrotropics. From samples collected in Ghana, we aim to resolve the cryptic diversity identified by mitochondrial (mt) DNA using nuclear genetic, acoustic, and external morphometric data. We confirmed the presence of four previously established mtDNA lineages within the H. caffer complex and found significant genetic divergence among lineages based on nuclear microsatellite data and significant differences in frequencies of echolocation calls and morphometric measures. From these new data, we conclude that H. caffer complex in West Africa consists of at least four distinct species. While the small‐sized species from coastal savanna could be assigned to H. caffer tephrus, the taxonomic identity of the three sympatric, similarly sized species pertaining to H. ruber from the forest zone of Central Ghana is yet to be assessed. Abstract : We investigated bats of the Hipposideros caffer complex from Ghana in order to resolve their cryptic diversity. We confirmed presence of four previously established mtDNA lineages and demonstrated significant divergence among them based on nuclear microsatellites, frequency distribution of echolocation calls, and external morphometry. We showed that H. caffer complex in West Africa consists of at least four distinct species and highlighted the potential presence of further cryptic species. Zusammenfassung: Die Artenvielfalt vieler Ökosysteme wird generell oft unterschätzt, insbesondere in den Tropen. Dies trifft besonders für Fledermäuse zu, bei denen sich, im Vergleich zu anderen Säugetiergruppen, zahlreiche morphologisch sehr ähnliche Arten finden. Wir untersuchten die westafrikanischen Vertreter des Hipposideros caffer ‐ Komplexes, einer in der gesamten Afrotropis verbreiteten Gruppe insektivorer Fledermausarten. Basierend auf Material aus Ghana untersuchten wir vier über mtDNA zuvor bereits identifizierte Linien mittels Kernmikrosatelliten‐Daten sowie akustischer und morphometrischer Daten. Unsere Ergebnisse bestätigen die Existenz von vier mtDNA‐Linien innerhalb des H. caffer ‐Komplexes und zeigen nun auch anhand von Kernmikrosatellitendaten eine signifikante genetische Divergenz der einzelnen Linien, sowie signifikante Unterschiede in Echoortungsfrequenzen und morphometrischen Parametern. Unsere neuen Daten belegen, dass der H. caffer ‐Komplex in Westafrika aus mindestens vier Arten besteht: Während relativ kleine Individuen der Küstensavanne Ghanas wohl zur Art H. tephrus gehören, kann die taxonomische Identität der drei ähnlich großen, sympatrischen Arten aus der Waldzone von Zentralghana, die aktuell H. ruber zugeordnet werden, bislang noch nicht abschließend beurteilt werden.